(untitled) (Research, Society and Development, 2024)
This article aims to study the indicators associated with dropout and discharge in psychotherapy by patients treated within the Brazilian Unified Health System (SUS), through a census conducted in a mental health outpatient clinic integrated with SUS and part of the care units of a university. Of an exploratory, retrospective, cross-sectional, documentary, and quantitative nature, the research began in 2019, analyzing the schedules of psychologists who worked at the outpatient clinic in 2017. With a sample of 252 patients, data were collected from schedules, case monitoring spreadsheets, and electronic medical records. Indicators were constructed to assess the care provided, and statistical analysis used chi-square tests and t-test for mean differences. Results revealed that 46% of patients dropped out of psychotherapy, 38% continued in treatment, 15% were discharged, and 1% were referred to other services. Indicators such as "no-shows" (p=0.000) and "qualification of the therapeutic plan" (p=0.016) showed statistically significant associations with treatment dropout. For the "discharge" outcome, there was a significant association with low severity of psychiatric diagnosis (p=0.04), a higher number of completed appointments (p=0.018), and a lower proportion of missed appointments (p=0.000). The mean number of completed appointments per patient who was discharged was 7.2 appointments. These analyses support trends observed in the literature regarding the importance of studying appointment scheduling flows, first appointment attendance rates, treatment dropout, and characteristics of psychological care in public health services.